Effect of size and shape on electronic and optical properties of CdSe quantum dots - Liu, Yincheng (2020)
In this paper, we used the 8-band k$·$p model with valence force field considerations to investigate the effect of size and shape on electronic and optical properties of cadmium selenide quantum dots. Major factors related to their properties including band mixing probabilities, spatial charge distributions, transition matrix elements and Fermi factors were studied. Volumetrically larger CdSe dots were found to have smaller band-gaps but higher transition matrix elements and Fermi factors. The maximum optical gain for dots was observed to have an initially positive and then negative correlation with their real-space size as a result of combined effects of various factors. For the shape effects, cubic dots were found to have smaller band-gaps, Fermi factors and transition matrix elements than spherical dots due to higher level of asymmetry and different surface effects. Consequently, cubic dots have lower emission energy, smaller amplification. The occurrence of near E1-H1 transition broadens the gain spectrum of cubic dots. Cubic and spherical dots are both proven to be promising candidates for optical devices under visible range. We have demonstrated that size and shape change could both effectively alter the properties of quantum dots and therefore recommend consideration of both when optimizing the performance for any desired application.